1995
DOI: 10.1007/bf00192108
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological criteria for intestinal neuronal dysplasia of the submucosal plexus (type B)

Abstract: The aim of this study was to review critically the diagnostic features of intestinal neuronal dysplasia type B (IND B). Over a period of 5 years colonic mucosal biopsies of 773 children with symptoms of chronic constipation were examined. Four biopsies taken 2-10 cm above the pectinate line were cut in serial sections and histochemical lactate dehydrogenase, succinate dehydrogenase, (SDH) and acetylcholinesterase (AChE) reactions performed. Presence of giant ganglia of the submucosal plexus, being characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 38 publications
2
71
0
7
Order By: Relevance
“…3,[5][6][7][8] Modified criteria evolved gradually, primarily because of a series of papers coauthored by Meier-Ruge in the mid-1990s that clarified in detail how enzyme histochemistry should be performed and ganglion cells counted. [7][8][9][10][11][12] During this period, Meier-Ruge and colleagues reported that abnormal AChE-positive innervation is an unreliable diagnostic feature after age 9 months, emphasized that submucosal ganglion cell hyperplasia was the key diagnostic feature of IND B, and commented that:…”
Section: History Of Ind Bmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[5][6][7][8] Modified criteria evolved gradually, primarily because of a series of papers coauthored by Meier-Ruge in the mid-1990s that clarified in detail how enzyme histochemistry should be performed and ganglion cells counted. [7][8][9][10][11][12] During this period, Meier-Ruge and colleagues reported that abnormal AChE-positive innervation is an unreliable diagnostic feature after age 9 months, emphasized that submucosal ganglion cell hyperplasia was the key diagnostic feature of IND B, and commented that:…”
Section: History Of Ind Bmentioning
confidence: 99%
“…These giant ganglia comprise only 3-5% of all ganglia seen in a given case and are usually not observed in the distal rectum (within 6-7 cm of the pectinate line). 9 Because of the latter observation, Meier-Ruge insists that diagnostic biopsies be obtained 8 to 10 cm proximal to the dentate line, 13 which is much farther from the anus than the typical biopsy used to rule out HSCR.…”
Section: History Of Ind Bmentioning
confidence: 99%
“…Наиболее характерными морфологическими его признаками являются гигантские нервные ганглии в подслизистом слое более чем с 8 нервными клетками (нормальный ганглий содержит от 2 до 4 нервных кле-ток). При этой патологии отмечено нарушение моторно-эвакуаторной функции кишки в различных вариантах: от легких запоров до клинической картины, имитиру-ющей болезнь Гиршпрунга [16,18]. Для постановки диагноза, который определяется как «количественный», нужно по крайней мере на 25-30 участках толстой киш-ки обнаружить от 4 до 7 гигантских ганглиев.…”
Section: клинический примерunclassified
“…В отли-чие от болезни Гиршпрунга, исследование довольно большого числа пациентов с интестинальной нейромы-шечной дисплазией типа В показало, что гиперплазия подслизистого сплетения и увеличение ацетилхолинэ-стеразной активности в нервных волокнах собственной пластинки слизистой оболочки зависит от возраста и может исчезнуть в процессе созревания нервной системы кишечника [1]. Провести дифференциацию между этой болезнью и незрелостью вегетативной нервной системы на первом году жизни крайне сложно [1,18,19]. ЗАКЛЮЧЕНИЕ У вышеописанных врожденных нарушений, как энте-ральной нервной системы, так и мышечной ткани стенки кишки, манифестирующих энтероколитом или перфо-рацией, гистологическая интерпретация порой бывает достаточно спорной и затруднительной.…”
Section: клинический примерunclassified
“…27 Intestinal neuronal dysplasia type B (IND B) has several features resembling ganglioneuromatosis, most importantly submucosal ganglia with more than six nerve cells. 28 No mention is made about the myenteric plexus. Whether IND B represents an entity or a secondary phenomenon has been much debated, 29 but is beyond the scope of this article.…”
Section: This Patient With a De Novo Ret Codon 918mentioning
confidence: 99%